2019
DOI: 10.3390/ijms20235837
|View full text |Cite
|
Sign up to set email alerts
|

Stay-Green Trait: A Prospective Approach for Yield Potential, and Drought and Heat Stress Adaptation in Globally Important Cereals

Abstract: The yield losses in cereal crops because of abiotic stress and the expected huge losses from climate change indicate our urgent need for useful traits to achieve food security. The stay-green (SG) is a secondary trait that enables crop plants to maintain their green leaves and photosynthesis capacity for a longer time after anthesis, especially under drought and heat stress conditions. Thus, SG plants have longer grain-filling period and subsequently higher yield than non-SG. SG trait was recognized as a super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 154 publications
5
77
0
1
Order By: Relevance
“…For example, stay green is an adaptive trait that provides better drought tolerance and nitrogen use efficiency in crops [ 56 , 159 ]. Research has shown that stay-green is a part of the drought adaptation mechanism that increases yield stability and lodging resistance in sorghum and other cereals, where it can lead to prolonged grain filling duration and improve yield [ 146 , 160 ]. Interestingly, other reports show that canopy temperature (CT)—an indicator of evaporative cooling from the canopy surface and an adaptive trait for high yielding and drought tolerance—is associated with stay green and deeper roots [ 161 ].…”
Section: Phenomic Characterization and Evaluation Of Genebank Accementioning
confidence: 99%
“…For example, stay green is an adaptive trait that provides better drought tolerance and nitrogen use efficiency in crops [ 56 , 159 ]. Research has shown that stay-green is a part of the drought adaptation mechanism that increases yield stability and lodging resistance in sorghum and other cereals, where it can lead to prolonged grain filling duration and improve yield [ 146 , 160 ]. Interestingly, other reports show that canopy temperature (CT)—an indicator of evaporative cooling from the canopy surface and an adaptive trait for high yielding and drought tolerance—is associated with stay green and deeper roots [ 161 ].…”
Section: Phenomic Characterization and Evaluation Of Genebank Accementioning
confidence: 99%
“…Canopy temperature can be measured by handheld [157,165] or airborne [166,167] thermal and hyperspectral imagery to screen crop genotypes for drought and heat adaptation. Stay-green is the plant's ability to retain their green leaves and photosynthetic activities for an extended period post-anthesis and is associated with enhanced drought and heat tolerance in various crop species [168]. Functional stay-green has been shown to link with deeper roots and cooler CT, which are adaptive traits for heat and drought adaptation, and higher yielding [169].…”
Section: Stomatal Conductance Canopy Temperature and Stay-greenmentioning
confidence: 99%
“…One consequence of delayed flowering is often the retardation of leaf senescence (Gan and Amasino, 1995;Wingler et al, 2010). Similarly, the BBX32OE-soya displayed an extended period of reproductive development associated with delayed leaf senescence thus contributing to the increased yield phenotype, similar to some "stay green" crop genotypes (Preuss et al, 2012;Kamal et al, 2019). While leaf senescence has not been measured in the BBX32-OE plants, nodes on the BBX32centric GRN include GOLDEN-LIKE2 (GLK2) and ACTIVATING FACTOR1 (ATAF1; also called NO APICAL MERISTEM ATAF1/2 CUP SHAPED COTYLEDON (CUC)2 (NAC2); Fig.…”
Section: Bbx32 Over-expressed In Arabidopsis and Soybeancontrol Of A mentioning
confidence: 99%